Service activities in developing countries : an analysis based on national accounts - Blades, Derek W.; Johnston, Derek D.; Marczewski, Witold (Paris : Development Centre of the Organisation for Economic Co-operation and Development, 1974)
The present study is the first of a series which will deal with practical problems of estimating various components of the national accounts.
Includes bibliographical references: p. 251-254.
ne 24/01/2019
Loans
Keywords: Service industries